Pemetaan Indikator Pertumbuhan Ekonomi Di Provinsi Sumatera Barat Menggunakan Analisis Korespondensi Berganda - Vidhiya Addini; Dony Permana; Nonong Amalita; Admi Salma (UNP Journal of Statistics and Data Science, 2024)
Economic growth is a key factor in sustainable regional development. This study employs Multiple Correspondence Analysis (MCA) to explore the relationships among economic growth indicators in the districts/cities of West Sumatra Province. Data from 2022 provided by the Central Statistics Agency are used to analyze economic growth indicators, including Gross Regional Domestic Product (GRDP) at Constant Prices (X1), Human Development Index (X2), Labor Force Participation (X3), Domestic Investment (X4), Government Expenditure (X5), and Balance Fund Allocation (X6). The results of MCA reveal complex relationships among these variables, with the first and second dimensions explaining approximately 44.43% of the data variance. The MCA plots visualize clusters of districts/cities based on their economic characteristics. From these plots, it is concluded that there are disparities in economic growth indicators in West Sumatra Province, with 11 districts/cities requiring special attention to achieve equitable and sustainable economic growth. This study contributes to a deeper understanding of regional economic disparities in West Sumatra Province and their relevance to more targeted and sustainable development policies.